2009
DOI: 10.1007/s12204-009-0354-2
|View full text |Cite
|
Sign up to set email alerts
|

An authenticated group key distribution scheme for wireless sensor networks

Abstract: In wireless sensor networks (WSNs), group key distribution is the core of secure communications since sensor nodes usually form groups and cooperate with each other in sensing data collection and in-network processing. In this paper, we present a scalable authenticated scheme for group key distribution based on a combinatorial exclusion basis system (EBS) for efficiency and one-way hash chains for authentication. The proposed scheme guarantees a lightweight authenticated group key updating procedure and is eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Finally, our study provides additional evidence concerning moderate to severe undernutrition, as it is significantly associated with poor postoperative outcomes, which is consistent with the results of previous studies identifying risk factors for recurrent HAEC and quality of life in patients with HSCR. 11 , 26 Ding et al reported the impact of preoperative nutrition support in patients with HSCR and refractory constipation. They demonstrated that at the 1‐month follow‐up, the incidence of postoperative complications was lower and nutrition status was significantly improved in the group of patients who received enteral nutrition (EN) for 2 weeks prior to surgery compared with those without EN support.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study provides additional evidence concerning moderate to severe undernutrition, as it is significantly associated with poor postoperative outcomes, which is consistent with the results of previous studies identifying risk factors for recurrent HAEC and quality of life in patients with HSCR. 11 , 26 Ding et al reported the impact of preoperative nutrition support in patients with HSCR and refractory constipation. They demonstrated that at the 1‐month follow‐up, the incidence of postoperative complications was lower and nutrition status was significantly improved in the group of patients who received enteral nutrition (EN) for 2 weeks prior to surgery compared with those without EN support.…”
Section: Discussionmentioning
confidence: 99%
“…As a structural member driven into the soil, the compressive stress dispersible recoverable anchor cable can transfer the tensile load to the anchored soil layer, strengthen the enclosure structure, control the displacement, and reduce the deformation of the foundation pit. The main components of the recovered bolt are the anchor, free section and anchoring section [25], as shown in Figure 2.…”
Section: Hot Melt Retrievable Anchor Cablementioning
confidence: 99%
“…However, the land-oriented competitiveness of ports in the Yangtze River Delta region to which Shanghai Port belongs has obvious differences, while the Pearl River Delta has become the region with the highest average land competitiveness among all regions thanks to the relatively strong performance of Guangzhou port and Shenzhen port. In terms of sea-oriented competitiveness, it presents the characteristics of spatial aggregation development, with the central region as a whole being stronger, while the north and south wings are weaker [25] . Shanghai Port has the strongest direct connectivity capability and occupies the first place in the dominance, while Ningbo Zhoushan Port has the greatest advantage in spatial accessibility.…”
Section: 31analysis Of Four Aspects Of Competitivenessmentioning
confidence: 99%